Non‐pharmacological interventions for pollen‐induced allergic symptoms: Systematic literature review. Issue 1 (10th November 2021) - Schutzmeier, Paul; Kutzora, Susanne; Mittermeier, Isabella; Becker, Jana; Bergmann, Karl‐Christian; Böse‐O'Reilly, Stephan; Buters, Jeroen; Damialis, Athanasios; Heinrich, Joachim; Kabesch, Michael; Mertes, Hanna; Nowak, Dennis; et al.
Abstract: Background: Allergic diseases pose a health problem worldwide. Pollen are widespread aeroallergens which can cause symptoms like shortness of breath, cough, itchy eyes, or rhinitis. Apart from preventive measures and pharmacological treatment, also non‐pharmacological interventions have been suggested to reduce symptoms. The objective of this work was to review studies investigating the effectiveness of non‐pharmacologic interventions to reduce allergic symptoms. Methods: PubMed, EMBASE, and CENTRAL were systematically reviewed in July 2018 and April 2020. Several authors worked on the screening of titles, abstracts, and full texts. One author for each literature search performed the data extraction and the risk of bias assessment. Studies were included if they met the inclusion criteria defined by the PECOs. Studies which investigating the effect of non‐pharmacologic interventions on patients with allergic rhinitis were included. Results: Twenty‐nine studies investigating eleven types of non‐pharmacologic interventions to avoid and reduce allergic symptoms due to pollen exposure were included in this review. Out of all studies, seven studies addressed nasal rinsing and 22 included acupuncture, air filtering, artisanal tears, individual allergen avoidance advice, various nasal applications, self‐hypnosis, rhinophototherapy, and wraparound sunglasses. Conclusion: Most studies had a high risk of bias and small sample sizes. There were only a few high‐quality studies that give hints about the effectiveness of non‐pharmacological interventions. For future research, more high‐quality studies are required to confirm the effectiveness of simple, safe, and cost‐effective interventions.